Implementation of Three-Phase Grid-Connected Inverter Controlled with dSPACE DS1103 - Isen, Evren; Yanik, Gurcan; Bakan, A. Faruk (IEEE, 2013)
In this paper, realization of three-phase grid-connected inverter controlled with dSPACE DS1103 control board is presented. Detailed information about power circuit, sensor board, signal isolation board and DS1103 is given in the paper. The inverter is controlled with DS1103 control board, programming the DSP via MATLAB/Simulink. Connection between the developed control algorithm in Simulink and experimental setup is made with installed DS1103 tools in Simulink. Space vector pulse width modulation technique in d-q synchronous reference frame is used to control the three-phase inverter. The transferred power to grid is 10 kW via three-phase inverter. The injected grid current has 3.59% THD value with 9 kHz switching frequency and 3 mH filter inductance.
Keywords: DS1103; grid-connected inverter; space vector pulse width modulation; three-phase inverter; Energy & Fuels